BIO-CONTROL EFFICACY OF MUTANTS TRICHODERMA VIRIDE AGAINST F.SP. FUSARIUM OXYSPORUM CICERI (Journal of Plant Disease Sciences, 2017)
In an attempt to develop superior isolates for Trichoderma viride improvement of bio-control efficacy, mutation was carried out. After application of different concentrations of ethyl methyl sulphonate (EMS) @ 100,150,200 and i.e. 250 µl/mlat time interval of 30, 45 and 60 minutes twelve Trichoderma viride mutants were obtained and tested for their antagonistic activities ( Efficient in vitro). mutants were tested up to six generations to check their stability. Among the mutants, four stable mutants , TVME 2b,TVME 2c,TVME 3c and TVME4c viz. were proved as effective antagonists against f.sp. on the Fusarium oxysporum ciceri basis of per cent growth inhibition. High chitinase enzyme units/mg of protein i.e. 0.64, 0.63, 0.63 and 0.60 respectively obtained from the same effective mutants.
Keywords: Mutation, ethyl methyl sulphonate (EMS), Chitinase, Trichoderma viride, Fusarium oxysporum ciceri f.sp.